Physik und Poetik - Heydenreich, Aura,Mecke, Klaus (De Gruyter, 2015)
Physics and literature are two forms of knowing the world that are both complementary and contingent. Poetical-physical ways of writing and metaphors in physical theories are two sides of a coin. Interviews with Ulrike Draesner, Durs Grünbein, Michael Hampe, Jens Harder, Reinhard Jirgl, Thomas Lehr, Ulrich Woelk, and Juli Zeh enrich our knowledge of these two cultures through voices familiar with both sides.
9783110417883
Keywords: Online-Publikation; Deutsch; Literatur; Physik